National Forest Restoration Projects in China: Cost‐Efficiency, and Trade‐Off Between Carbon Sequestration and Water Consumption - Jiehao Zhang; Yulong Zhang; Xia Wang; Tiehu He; Huijuan Xia; Kerong Zhang; Quanfa Zhang (Earth's Future)
Abstract International initiatives, such as the Bonn Challenge, Trillion Tree Campaign, New York Declaration on Forests, and United Nations Decade on Ecosystem Restoration, have set ambitious targets for forest restoration. However, the effectiveness and cost‐efficiency of large‐scale forest restoration projects (FRP) in different climatic zones, and the trade‐off between carbon sequestration and water consumption caused by FRP are poorly understood. Here, we conducted a comprehensive examination of 2,778 counties in China, where the world's most ambitious FRP was executed during the past two decades. Results showed that, on average, each square kilometer of FRP yielded an additional 0.6 square kilometers of forests and contributed an extra 1354.9 tC to forest carbon storage, with the aridity index emerging as a key influencer. The actual expenditure incurred per ton of increased forest carbon storage amounted to approximately 118.9 USD in average, with the lowest in Southwest at 50.9 USD. The expansion of forest cover and enhanced biomass storage led to a notable increase in water consumption, and the trade‐off was particularly pronounced in arid regions. Our study provides empirical evidence that FRP is an effective and cost‐efficient climate change mitigation strategy for humid climate zones under current carbon prices. However, FRP is not cost‐efficient in semi‐arid and arid regions. These findings have significant implications for global forest restoration endeavors and formulating sound climate change mitigation policies.